2020
DOI: 10.1016/j.cub.2020.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Key Male Glandular Odorants Attracting Female Ring-Tailed Lemurs

Abstract: Highlights d During the breeding season, females are attracted by male wrist glandular odor d Three C12 and C14 aldehydes are seasonally secreted by the male antebrachial gland d The amounts of the identified aldehydes increase in a testosterone-dependent manner d Females are interested in cotton pads soaked in the identified aldehydes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
30
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 26 publications
3
30
1
Order By: Relevance
“…Might the apparent seasonal difference in male gland secretion levels reflect breeding season testosterone titres and could this be experimentally manipulated? Shirasu, Ito and colleagues [5] injected two males in the non-breeding season with testosterone, which, they report, raised the candidate antebrachial gland molecules to breeding season levels.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Might the apparent seasonal difference in male gland secretion levels reflect breeding season testosterone titres and could this be experimentally manipulated? Shirasu, Ito and colleagues [5] injected two males in the non-breeding season with testosterone, which, they report, raised the candidate antebrachial gland molecules to breeding season levels.…”
mentioning
confidence: 99%
“…However, despite evidence that smell is used for communication in primates, no primate pheromones have been chemically identified so far (despite claims for human pheromones [4]). A recent study in Current Biology by Mika Shirasu, Satomi Ito, Kazushige Touhara and colleagues [5] claims to have identified female-attracting odorants in male ring-tailed lemurs (Lemur catta). Their proposal has been questioned in this issue of Current Biology by Christine Drea and colleagues [6] and Peter Kappeler [7] -to which Shirasu, Ito and colleagues respond [8,9].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As a result our current understanding of chemical signals in callitrichids is more complex and nuanced than it was when we first started this study 40 years ago.Although mammalian signals have multiple chemical components, it is still possible that one or a few compounds are responsible for influencing behavior. A recent study on ring-tailed lemurs (Lemur catta) byShirasu et al (2020) found three main components in male scents that were effective in attracting attention of females. The three components acted synergistically to produce a stronger response than any single component.…”
mentioning
confidence: 99%